(3Md GdeTcdGJ ef EJMGa Phi GdMGLGJs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s
(3ChdgG (B:s
(3hHYO , ajbhd CMeO Hf YHOGdefYe GdOefghQi ef Ydjg HGdQVi s
(3BNQgG (B:s
(3hUMHg GSe LeY dUGMH HeYfi GdUMGHi hgh ef GLJeY Hg Udi Gddg Ydjg hSde s
(3HgG LOGhd JhVjMjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B303s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs